Rancang Bangun Sistem Digitalisasi Pengarsipan (E-SIP) Berbasis Website - Darusman, Calvin Dicky; Amaliyah; Dimisqiyani, Erindah (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
An organization can never be separated from administrative activities. Archives are an activity that cannot be separated from administrative activities. Archives play an important role for organizations because archives are used to store and maintain important records or documents related to the organization’s activities. Apart from that, archives also help organizations to avoid the risk of losing information or documents that could be considered valuable. By having well-organized archives, organizations will find it easier to access the information they need. In the past, archives were managed manually, such as notebooks and documents which were still in the form of paper, which required storage space and required time in the search process. Therefore, nowadays many organizations choose to switch to digital archiving, which is an easier and faster process than manual archiving. Archives management at BRIDA East Java Province has not been carried out using a digital system. To minimize risks in archival storage, it is better to change the manual records management system to a digital archive. The preparation of this final assignment used qualitative research methods. Qualitative research usually collects data by conducting observations, interviews, and documenting research activities. Because archiving in BRIDA East Java Province is still done manually, in this research a website-based design idea called Electronic Archives (E-SIP) was designed to simplify the digital archiving process. With the creation of this design, it is hoped that it will facilitate the management of archives at BRIDA East Java Province and that archiving can be carried out digital.